2014
DOI: 10.12689/jmep.2014.203
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Antecedents of Proactive and Reactive Rebelliousness: The Role of Parenting Style, Childhood Adversity, and Attachment

Abstract: Adolescence is a time of developmental transition that for one in five young people is characterised by feelings of oppositionality, rebellion, and negativism. Despite the prevalent experience of teen turbulence and despite its significance within the phenomenological framework provided by reversal theory (RT), the childhood antecedents of rebelliousness in adolescence and adulthood have not been given extensive empirical attention within RT, although such work has been carried out using other constructs and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
2
1
Order By: Relevance
“…Care was important only for the Resistance to Proximity dimension. This result is distinct from the current parental style literature, which focus most of the time only in Care, or in their joint influence of Control and Care (Wilhelm, Gillis & Parker, 2016;Kokkinos, 2013;McDermott & Barik, 2014;Timpano et al, 2015).…”
Section: Rachel Coelho Ripardo Eulina Da Rocha Lordelocontrasting
confidence: 83%
See 2 more Smart Citations
“…Care was important only for the Resistance to Proximity dimension. This result is distinct from the current parental style literature, which focus most of the time only in Care, or in their joint influence of Control and Care (Wilhelm, Gillis & Parker, 2016;Kokkinos, 2013;McDermott & Barik, 2014;Timpano et al, 2015).…”
Section: Rachel Coelho Ripardo Eulina Da Rocha Lordelocontrasting
confidence: 83%
“…Bourne et al (2014) found that adult attachment avoidance was significantly negatively correlated with perceived paternal care, and adult anxious attachment was significantly positively correlated with paternal overprotection, but no relationships were found between maternal subscales and adult attachment. Low care and high controlling childhood is usually associated with discomfort with being close and intimate, thus preventing relationships in adulthood (Manassis, Owens, Adam, West, & Sheldon-Keller, 1999;McDermott & Barik, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation